Comparison of the Effects of Dienogest and Leuprolide Acetat on Serum Interferon (IFN-Æ”) Levels in a Mouse Model of Endometriosis (Mus musculus) - Maria Antonia Barbara Batu Mali; Siskanita Nur Fitriana; Sutrisno Sutrisno; Husnul Khotimah; I Wayan Arsana Wiyasa; I Wayan Agung Indrawan; Maharani Maharani (Asian Journal of Health Research, 2023)
Introduction: Endometriosis is a medical condition in which there is abnormal growth of tissue resembling the endometrium outside the uterus. It can cause symptoms of pain and/or infertility. The current medical therapy focuses on reducing estradiol levels or stimulating progesterone response. One of the most effective options for medical treatment is the use of GnRH analogs. Dienogest have a direct anti-inflammatory effect on endometriotic stromal cells. However, a comparison of the anti-inflammatory effects of these drugs on IFN-Æ” has not been previously investigated. Therefore, this study aims to compare the effects of reducing IFN-Æ” by both Dienogest and Leuprolide Acetat in a mouse model. Material and Methods: This study employed a post-test only control group design and involved 4 groups, namely the negative control group, positive control group, and two treatment groups: one group administered Dienogest at a dosage of 0.0052 milligrams per day for 14 days, and the other administered Leuprolide Acetat at a dosage of 0.00975 milligrams once every 5 days for a period of 14 days. Serum IFN-Æ” levels were measured using Enzyme-Linked Immunosorbent Assay (ELISA). The data were subsequently analyzed using IBM SPSS 25 with One-Way ANOVA test. Results: This study demonstrated that Leuprolide Acetat significantly decreased serum levels of IFN-Æ”, whereas Dienogest actually increased the levels . Conclusion: In a mouse model of endometriosis (Mus musculus), Leuprolide Acetat effectively reduced the levels of IFN-Æ” (pro-inflammatory). Conversely, Dienogest increased the levels of IFN-Æ” (anti-inflammatory) in the mouse model of endometriosis.